Auditors’ Perspective of Audit Quality during the COVID-19 Pandemic: Evidence from the United Arab Emirates - Grassa, Rihab; Obaidalla, Ibrahim; Hamza, Mouna (Indonesian Journal of Sustainability Accounting and Management, 2022)
During the coronavirus disease 2019 (COVID-19) pandemic, external auditors have faced unforeseen logistical challenges as they had to audit financial statements remotely. Definitively, the new circumstances had various impacts on audit quality. This study explores the effect of social distancing owing to the COVID-19 outbreak on the quality of financial audits in the United Arab Emirates. To this end, we conducted 11 semi-structured interviews with audit partners and directors from BIG 4 audit firms. The findings from the content analysis of these interviews show that during the pandemic, external auditors faced different challenges in maintaining the quality of financial audits. Indeed, the lockdown imposed by the pandemic has largely affected materiality and risk assessments, audit procedures and collection of evidence, and auditors’ performance and efficiency efforts. It also increased cyber risk. These conclusions stress the importance of investing in blockchain and artificial intelligence to resolve similar challenges in the future. Blockchain technology would, in fact, be an ultimate solution in similar circumstances as it permits enhancing the efficiency and adaptability of communication between auditors and auditee firms, which can in turn promote the quality of the financial reporting and audit.